Caracterização biogeoquímica de ecossistemas amazônicos: rios e lagos selecionados das microrregiões Bragantina, do Salgado e Guajarina - PA - MENEZES, Lúcia Beckmann de Castro (Universidade Federal do Pará, 2017)
It was compared physical, chemical, physical-chemical and hydrobiological environmental parameters of waters and of aquatic humic material, in three kind of places seemingly identified, because these parameters are excellent indicators of biogeochemical and ecophysiological characteristics of aquatic ecosystems, in the attempt of characterizing the influence of the biogeochemical factors of pollution, the anthropogenic influence and the studied ecosystems productivity. It was collected samples in the course of the Guama river, in Ourem – Bragantina zone (high course), in Bujaru (medium course) and in Belem - Guajarina zone (close to estuary), as well as in two lakes of coastal plain located in the island of Atalaia (Salinopolis), and still in the Arapepo river (municipal district of Salinopolis – Salgado zone), this one under strong influence of the waters of the Atlantic ocean, in the months of December of 1996 (drought period), May of 1997 (rainy period) and October of 1997 (drought period). The methods used in the characterization involved physical-chemical analysis and chemical analysis for the determination of the chemical composition in relation to the dominant ions and the indicators of the presence and of the decomposition of the organic matter (humic material) and hydrobiological analysis, for chlorophyll evaluation, in natural waters, submitted or not to an anthropic action. It was utilized the ultraviolet and visible spectrophotometry and in the infra-red spectroscopy to the characterization of the natural organic matter, where the humic acid and fulvic acid prevail. The spectra in the ultraviolet-visible were also used for the identification of the chlorophyll. The analytic results have showed a clear difference among the studied ecosystems, suggesting an influence of an anthropic action in the Guama river, which characterizes the lakes in Salinopolis as an ambient with high amount of organic matter (humic substances) and the Arapepo river presenting results very differents due to the oceanic influence and to the occurrence of mangroves in its margins, being the only ecosystem where the occurrence of photosynthetics pigments were perceived (chlorophyll). The calculation of the ionic relation indicated the presence of marine intrusion in the environments of the lakes I and II, Arapepo river and Guama river (Belem). The seasonal was reflected intensively in the three studied ambients, through parameters as color, turbidity, specific conductivity, chloride, sulfate, organic matter (consumed oxygen), iron and the larger cations (calcium, magnesium, sodium and potassium), notedly in the physiografic area of the Salgado zone. The relation carbon/nitrogen observed for the humic substances suggests that the humic material of the lakes has an older formation than the rivers. The rate E4/E6 obtained through the spectra in the ultraviolet-visible indicates that the humic and fulvic acids present in the samples have a high aromaticity. The interpretation of the spectra of absorption in the area of the infra-red, has permitted to verify that there are present the most characteristic bands, indicating the presence of groups C-H, C=O and COOH and also of aromatic skeleton and suggesting the formation of humic substances - metal complex, what is in conformity with the analytic results obtained for metals in the humic material. The amount of metals (iron, manganese, copper, chromium and zinc) presents in the humic material were always larger in the samples of the Guama river (Belem), what suggests enrichment due to anthropogenic influence.